How to teach handwriting - Vlasenko, Ludmila; Chala, Kateryna (My University, 2012)
Handwriting does not have to be a battleground. By targeting specific and narrow objectives, praising efforts that are well-done as well as pointing out errors to be corrected, and scheduling regular, supervised practice, progress can be made much more rapidly than if children are left on their own to complete handwriting workbooks. Young children want to write well, but they are often frustrated by their own lack of coordination and discouraged because it requires more effort to please either the teacher or themselves than they thought it would. Older students often rush to complete assignments and argue that neatness is irrelevant. In either case, the teacher must be patient, choose reasonable objectives, and stand firm.
Keywords: почерк; почерк; handwriting; мета; зусилля; практика; помилка; прогрес; координація; навик; розвиток; пам'ять; развитие; память; objective; effort; practice; error; correct; progress; write; coordination; skill; development; memory; кафедра ділової іноземної мови та міжнародної комунікації; кафедра іноземних мов професійного спрямування